Association of HindIII SNP in Intron 19 of the FVIII gene with musculoskeletal complications in pediatric patients with hemophilia A - Larasati, Maria Christina Shanty; Endaryanto, Anang; Nugraha, David; Basuki, Sukmawati; Rantam, Fedik Abdul; Ugrasena, I Dewa Gede (Journal of Neonatal Surgery, 2025)
Hemophilia A (HA) is the most common congenital X-linked coagulopathy caused by mutations in the FVIII gene, inherited in a recessive manner. Despite its well-established clinical characteristics, approximately 30% of HA cases are sporadic. Musculoskeletal complications, such as recurrent joint bleedings, significantly impact patient quality of life. This study aimed to investigate the relationship between the HindIII polymorphism in the FVIII gene and musculoskeletal complications, as well as its association with family history in HA patients from East Java, Indonesia. A total of 63 patients were analyzed using the PCR-RFLP method. The findings revealed no significant correlation between the HindIII SNP and musculoskeletal complications (P = 0.720) or family history (P = 0.542). These results suggest that the HindIII polymorphism does not serve as a determinant factor for musculoskeletal complications or family history in this population. Further studies with larger sample sizes and advanced molecular techniques are needed to explore the role of the HindIII polymorphism in hemophilia A.